The effect of neonatal administration of oleanolic acid on health outcomes associated with diet-induced metabolic dysfunction in rats - Nyakudya, Trevor Tapiwa (My University, 2018)
The neonatal period is a critical window of developmental plasticity. Consumption of fructose-rich diets has been implicated in the increasing global prevalence of metabolic dysfunction (MD) and non-alcoholic liver disease (NAFLD). Interventions during periods of early ontogenic developmental plasticity can induce epigenetic changes which program metabolism for positive health benefits later in life. The phytochemical, oleanolic acid (OA) possesses anti-diabetic, anti-oxidant and anti-obesity effects. I investigated the potential protective effects of neonatal oral administration of OA on the subsequent development of health outcomes associated with fructose-induced MD and NAFLD in male and female rats. The study was divided into two major experiments. In the first short-term experimental study, the potential of neonatal oral administration of OA to acutely protect against the development of fructose-induced oxidative damage, adverse general health outcomes and precocious maturation of the gastrointestinal tract (GIT) in suckling male and female rats was investigated. Male and female suckling rat pups (N=30) were randomly assigned to four groups and gavaged daily with 10 mℓ/kg body mass of: distilled water (DW) with 0.5% (v/v) dimethyl sulphoxide (vehicle control), oleanolic acid (OA; 60 mg/kg), high fructose solution (HF; 20% w/v), or OAHF for 7 days. On day 14, the pups were euthanised. Blood, liver and skeletal muscle samples were collected to determine clinical health profiles, hepatic lipid content and gene expression of anti-oxidant enzymes, superoxide dismutase (SOD2) and glutathione peroxidase (GPx1). Rats in all groups had a significant increase in body mass over the seven day treatment period (ANOVA; P<0.05). There were no significant differences in visceral organ masses, general clinical health profiles, liver lipid content and GIT morphometry across all treatment groups (ANOVA; P>0.05). Neonatal oral administration of fructose lowered the expression of genes for anti-oxidant enzymes (SOD2 and GPx1) which was prevented by OA (ANOVA; P<0.05). Findings from this study provide evidence that short-term neonatal oral administration of OA protects against fructose-induced oxidative damage with seemingly no adverse effects on health or the maturational and developmental changes of the gastrointestinal tract in suckling male and female pups. In the second long-term experimental study, which was further subdivided into two studies, I investigated the potential protective effects of neonatal oral administration of OA on the subsequent development of high fructose diet-induced a) metabolic dysfunction and b) NAFLD in male and female rats. Male and female suckling rats (N=112) were randomly assigned into four groups and gavaged daily with 10 m mℓ/kg body mass of: distilled water (DW) with 0.5% (v/v) dimethyl sulphoxide (vehicle control), oleanolic acid (OA; 60 mg/kg), high-fructose solution (HF; 20% w/v) and OAHF for 7 days. On day 21, the rats were weaned onto normal rat chow and plain drinking water up to day 55. From day 56, half of the rats in each treatment group were continued on plain water whilst the remainder were given a high fructose solution (20 % w/v) as drinking fluid ad libitum for eight weeks. On day 110 the rats were subjected to an oral glucose tolerance test (OGTT) and then euthanised on day 112. Fasting glucose, triglyceride levels and terminal body mass were measured before termination. Blood samples were collected to determine the effects of treatments on fasting levels of cholesterol, insulin, glucose, triglycerides, insulin resistance (HOMA-IR), glucose tolerance (area under the curve for OGTT), a surrogate biomarker of liver function, alanine amino transaminase (ALT) and non-tissue specific alkaline phosphatase (ALP). Body adiposity was determined by measuring visceral and epidydimal fat pad masses. Liver samples were used to measure hepatic lipid accumulation and hepatic histomorphometry. The livers were formalin fixed, paraffin embedded and sectioned at 3μm. The sections were stained with haematoxylin and eosin for assessment of inflammation and Masson’s trichrome for visualisation of connective tissue and steatosis. Male and female rats in all groups of the second experiment had a significant increase in body mass over the study period (ANOVA; P<0.05). In the general metabolic dysfunction study, rats which consumed fructose as neonates and then later as adults (HF+F) and those which consumed fructose only in adulthood (DW+F) had significant increases in terminal body mass (females only), visceral fat mass (males and females), serum triglycerides (females only), epididymal fat (males only), fasting plasma glucose (males and females), impaired glucose metabolism (females only), β-cell dysfunction and insulin resistance (males and females) compared to the other treatment groups (P<0.05). There were no differences in fasting cholesterol levels across all treatment groups in both male and female rats (P>0.05). The sub-study on NAFLD revealed that fructose consumption in adulthood following neonatal fructose intake (HF+F) caused a 47-49% increase in hepatic lipid content of both male and female rats (P˂0.05). However, fructose administered in adulthood only (DW+F), caused a significant increase in liver lipid content in females only (P<0.05). NAFLD activity scores for steatosis were higher in male (HF+F) and female (DW+F and HF+F) rats compared to other treatment groups (P<0.05). Scores for inflammation were higher in female rats that received DW+F and HF+F (P<0.05) but not in male rats (P>0.05). NAFLD area fraction for fibrosis was 3 times higher in male and female rats that received a double hit neonatally and in adulthood (HF+F) and a late hit of fructose (DW+F) compared to the rats in the negative control group (P<0.05). I have shown that administration of a high fructose diet had adverse effects on several health outcomes associated with MD and induced NAFLD. However, it was notable that the timing of the fructose intake in the life stage of rats had an impact on the development of MD and NAFLD phenotype. I also observed sex-specific differences in the metabolic response to dietary fructose, with females appearing to be more vulnerable to the development of MD and NAFLD. It is thus important to note that studies should not just focus on a single sex but should be comparative between the sexes. I have also demonstrated, for the first time, that neonatal oral administration of oleanolic acid protects against the subsequent development of fructose-induced health outcomes associated with metabolic dysfunction and NAFLD by reducing hepatic lipid storage, terminal liver masses and hepatic histomorphological changes associated with NAFLD. I conclude that neonatal interventional treatment with oleanolic acid during the critical window of developmental plasticity protected against the development of fructose diet-induced adverse health outcomes associated with MD and NAFLD in male and female Sprague Dawley rats. Therefore, OA is a phytochemical that exhibits potential in the prevention of neonatal programming of MD and NAFLD later in life. OA should be considered as a natural strategic prophylactic intervention during periods of developmental plasticity with a lot of potential in the fight against the scourge of metabolic disorders that have a significant negative impact on the health systems globally.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, School of Physiology, fulfilment of the requirements for the degree of Doctor of Philosophy (PhD). Johannesburg, South Africa, 2018.
Keywords: Diet therapy; Nutrition; Infant care